ANALISIS KEUNGGULAN KOMPETITIF INDUSTRI JUAL BELI BESI BEKAS PADA UD. MULTI BAJA KUIN CERUCUK BANJARMASIN - Akhmad Supriyanto; Widyarfendhi Widyarfendhi; Ilyas Salafuddin (Universitas Ahmad Dahlan, 2019)
This research aims to identify the effect of key success factors (KSFs) of scrap metal buying-selling industry in Kuin Cerucuk Village Banjarmasin and value chain activities to the competitive advantage of UD. Multi Baja.The population in this study are the UD. Multi Baja Kuin Cerucuk Village Banjarmasin. The sampling technique used is the census method which means that all members of the population are used as samples. The secondary and primary data analyzed are company profiles, value chain, industry analysis and competitive advantage.The results shows that the company value chain activities is the source of competitive advantage which contained in the activities of the company such as, logistics activities cost drivers, operations, company infrastructure, marketing and sales. The key success factors (KSFs) of the industry consist of: economies of scale in the form of product attributes, distribution channels and working capital capabilities are influencing the competitive advantage of the industry. While human resources and technology have moderate influence. This competitive advantage is obtained from the implementation of a low cost strategy and integrated differentiation.